Infância e criança: um estudo no reassentamento urbano coletivo (RUC) São Joaquim, Altamira - PA - CAVALCANTE, Taynara Aparecida de Sousa (2022)
The construction of the Belo Monte Hydroelectric Plant (UHE Belo Monte) generated significant social and cultural changes in the municipality of Altamira-Pará, altering the daily lives of children living in areas classified as risk and social vulnerability zones. These children, along with their families, were relocated to the so-called Collective Urban Resettlement (RUC), which implied changes in their ways of being and living their childhood. In this sense, we sought to analyze how children (res)mean childhood in this new housing scenario. This is an ethnographic research with a qualitative approach, carried out with fifty children from six to twelve years old. The results demonstrate that the relocation of children and, consequently, the breaking of bonds, unfolded in diversified daily experiences and experiences, resulting in new spatial arrangements and, above all, in new ways of being and being in different places. However, the new spatial arrangements, built by the children, show the dialogic existence between the social and cultural dimension in a unique and significant way for the subjective, affective and human interaction aspects.